Growth and impurity characterization of AlN on (0001) sapphire grown by spatially pulsed MOCVD. Issue 4 (12th February 2016) - Chung, Roy B.; Rodak, Lee E.; Enck, Ryan W.; Sampath, Anand V.; Wraback, Michael; Reed, Meredith L.
Abstract : The reduction of undesirable gas phase reaction between trimethylaluminum and NH3 was achieved by spatially separating the precursors using N2 purge line during AlN growth by metal organic chemical vapor deposition (MOCVD). Under this condition, it was shown that the growth pressure has a strong impact on the surface morphology independent of pre‐reaction. For 0.8‐μm‐thick AlN grown on (0001) sapphire substrates, increasing pressure from 200 to 500 Torr drastically increased a root‐mean‐squared surface (r.m.s.) roughness from 0.48 to 33 nm. This morphological change was previously attributed to the pre‐reaction. Less pre‐reaction also allowed us to investigate the pressure dependence of impurity (carbon and oxygen) incorporation in AlN as the growth rate was no longer affected by the pressure. Unlike GaN, the carbon level almost doubled with increasing pressure from 200 to 500 Torr. By optimizing the surface morphology (r.m.s. roughness from 33 to 0.62 nm) at 500 Torr, the carbon concentration in AlN decreased from 5 × 10 18 to 7 × 10 17  cm −3 . Although there was no improvement in the structural quality, this uniquely designed MOCVD could further improve the material quality of AlN by reducing the impurity level.